2018
DOI: 10.22435/blb.v13i1.256
|View full text |Cite
|
Sign up to set email alerts
|

Preferensi Aedes aegypti Meletakkan Telur pada Berbagai Warna Ovitrap di Laboratorium

Abstract: Dengue Haemograffic fever is a vector borne disease which caused outbreaks and death. There is no applied vaccine until now, so the effort of prevention and control is to terminate chain of infection mosquito breeding. Factors which influenced  the female mosquitoe to lay their eggsare type of container, color, water, temperature, water source, humidity and environment condition. This study was conducted to determine the preferences of Ae. aegypti mosquitoes to lay aggs in various colors ovitrap in the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
1
1
0
6
Order By: Relevance
“…This finding is in line with studies in Bengkulu and Sri Lanka, which showed that female Aedes aegypti mosquitoes were more likely to lay their eggs in dark containers (45)(46). It is also in line with research that shows a tendency for mosquitoes to prefer laying eggs in black containers compared to other colors (41). Likewise, research conducted in the Banyumas region shows that Aedes albopictus prefer black plastic bottles or cups to other materials (23).…”
Section: Ovitrap Color Modification and Ovitrap Trap Abilitysupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is in line with studies in Bengkulu and Sri Lanka, which showed that female Aedes aegypti mosquitoes were more likely to lay their eggs in dark containers (45)(46). It is also in line with research that shows a tendency for mosquitoes to prefer laying eggs in black containers compared to other colors (41). Likewise, research conducted in the Banyumas region shows that Aedes albopictus prefer black plastic bottles or cups to other materials (23).…”
Section: Ovitrap Color Modification and Ovitrap Trap Abilitysupporting
confidence: 85%
“…These two organs can detect the place or point of laying eggs, food sources, identification of mosquitoes, distinguishing enemies (predators), and finding the opposite sex. The mosquito's compound eye (ommatidium) also has photoreceptor organs that can distinguish colors (41). From various studies, it is known that the female mosquito Aedes sp.…”
Section: Ovitrap Color Modification and Ovitrap Trap Abilitymentioning
confidence: 99%
“…Kedua aspek ini memiliki makna yang penting bagi program pengendalian vektor dan penyakit DBD karena hingga saat ini belum ditemukan obat bagi penyakit ini walaupun vaksin Dengue sudah diproduksi namun hingga saat ini belum diaplikasikan di Indonesia. 7 Dua [14][15][16] Hasil penelitian ini sejalan dengan penelitian Ambarita yang menemukan bahwa kontainer yang paling dominan ditemukan jentik adalah bak mandi, ember, dan drum. Hal yang sama juga ditemukan pada penelitian Prasetyowati, menyebutkan bahwa kontainer yang paling dominan adalah ember dan dispenser.…”
Section: Pendahuluanunclassified
“…Sebagai contoh, nyamuk Aedes spp. betina lebih menyukai benda atau kontainer yang berwarna gelap dengan air jernih untuk bertelur (16,18,19). Setiap nyamuk memiliki tempat perkembangbiakkan dengan ciri yang berbeda.…”
Section: Pendahuluanunclassified